دور جهاز العرض الإلكتروني في التعليم الجامعي ومنعكساته التربوية والنفسية على بعض المتغيرات. ـ دراسة ميدانية على طلبة الكليات الطبية في جامعة تشرين ـ - علي, خضر; صبيرة, فؤاد (Latakia University Journal - Arts and Humanities Sciences Series, 2015)
هدفت الدراسة إلى تعرّف دور جهاز العرض الإلكتروني Data show في تعليم طلبة المرحلة الجامعية الأولى وفقاً لمتغير النوع (الجنس)، وتخصص الدراسة، ومستوى مهارات استخدام الحاسوب في الكليات الطبية بجامعة تشرين (التمريض، والصيدلة، والطب البشري). وصممت استبانة خاصة لهذا الغرض تضمّنت بعض المعلومات العامة و(19) بنداً موزّعاً على أربعة أبعاد (محاور). وزّعت الاستبانة على عينة عشوائية طبقية بلغ عددها (287) طالباً وطالبة. وقد أظهرت نتائج الدراسة أن لجهاز العرض الإلكتروني دوراً كبيراً من الناحية التربوية في تفاعل طلبة الكليات الطبية في أثناء شرح المحاضرة، وفي زيادة كمية المعلومات المقّدمة ونوعيتها ، وتبيّن أيضاً أثرٌ إيجابيٌ لهذه التقنية التعليمية الحديثة في احتفاظ الطلبة بالمعلومات المقدّمة بوساطتها، وفي تحصيلهم الدراسي بشكلٍ عام. وأشارت النتائج إلى عدم وجود فروق دالة إحصائياً تعزى لمتغيّري النوع (الجنس) ومهارات استخدام الحاسوب. بينما أظهرت وجود فروق دالة إحصائياً بين متوسطات درجات طلبة كلية التمريض مقارنة بمتوسطات درجات طلبة كليتي الطب البشري والصيدلة لصالح طلبة كلية التمريض. واقترح الباحثان إجراء مزيد من البحوث حول دور استخدام هذه التقنية الحديثة في كليات أخرى (كالكليات الهندسية والعلوم والآداب) وتبعاً لمتغيرات مختلفة كالسنة الدراسية، ورغبة الطالب في اختيار تخصص الدراسة، إذ إنَّ اختيار الطالب لفرع دراسته قد يتأثّر بطرائق التدريس والتقنيات المتبعة فيها. The study tries to identify the role of Data show in the education of undergraduate students, according to the variable type (gender) and the level of computer skills in the medical faculties at the University of Tishreen (nursing, pharmacy, human medicine). A questionnaire of 19 items is designed for this purpose, dealing with four areas of interest. It was distributed to a random sample of (287) students. Results of the study showed that the Data show had a major psychological and educational effect in terms of the interaction of medical faculties students during lectures, and increased the quantity and quality of information provided. Results also showed that this modern educational technology had a positive effect in terms of storing the information by students as well as in terms of their achievement. There were no statistically significant differences due to the variables of gender and computer skills. However, there was a statistically significant difference between the mean scores of the Faculty of Nursing students compared with grades averages of students in faculties of Medicine and Pharmacy in favor of the Faculty of Nursing students. The researchers suggested further research be made in other faculties at the university, depending on different variables such as the year of the study and students' choice of specialization, because the teaching methods and techniques may be affected by the student's choice of a branch of study.